Learning adaptability facilitates self-regulated learning at school: the chain mediating roles of academic motivation and self-management - She, Chunmei; Liang, Qiao; Jiang, Wenjun; Xing, Qiang (Frontiers in Psychology, 2023)
Studies have demonstrated that learning adaptability has emerged as an important factor for students’ utilization of self-regulated learning for successful learning, but how this association occurred is not clear yet. This study aimed to clarify the mechanism of the relationship between learning adaptability and self-regulated learning by investigating the chain mediating roles of academic motivation and self-management of 787 junior high school students under the “double reduction” background. The results showed that (1) learning adaptability had significant positive effects on junior high school students’ self-regulated learning and (2) academic motivation and self-management played independent and accumulative mediating roles in the relationship between learning adaptability and self-regulated learning. These findings help to understand how to support students in successfully coping with the new challenges brought by educational reform and promote effective adjustment to challenges, including the “double reduction”. The key contribution of this study is to provide new insights into the literature that academic motivation and self-management separately and sequentially mediate the learning adaptability, self-regulated learning links, and learning adaptability is effective driver of self-regulated learning in the population of junior high school students.